Extending Miscanthus Cultivation with Novel Germplasm at Six Contrasting Sites - Kalinina, Olena; Nunn, Christopher; Sanderson, Ruth; Hastings, Astley F. S.; van der Weijde, Tim; Özgüven, Mensure; Tarakanov, Ivan; Schüle, Heinrich; Trindade, Luisa M.; Dolstra, Oene; Schwarz, Kai-Uwe; Iqbal, Yasir; et al. (Frontiers in Plant Science, 2017)
Miscanthus is a genus of perennial rhizomatous grasses with C4 photosynthesis which is indigenous in a wide geographic range of Asian climates. The sterile clone, Miscanthus × giganteus (M. × giganteus), is a naturally occurring interspecific hybrid that has been used commercially in Europe for biomass production for over a decade. Although, M. × giganteus has many outstanding performance characteristics including high yields and low nutrient offtakes, commercial expansion is limited by cloning rates, slow establishment to a mature yield, frost and drought resistance. In this paper, we evaluate the performance of 13 novel germplasm types alongside M. × giganteus and horticultural ‘Goliath’ in trials in six sites (in Germany, Russia, The Netherlands, Turkey, UK and Ukraine). Mean annual yields across all the sites and genotypes increased from 2.3 ± 0.2 t dry matter ha−1 following the first year of growth, to 7.3 ± 0.3, 9.5 ± 0.3 and 10.5 ± 0.2 t dry matter ha−1 following the second, third and fourth years, respectively. The highest average annual yields across locations and four growth seasons were observed for M. × giganteus (9.9 ± 0.7 t dry matter ha−1) and interspecies hybrid OPM-6 (9.4 ± 0.6 t dry matter ha−1). The best of the new hybrid genotypes yielded similarly to M. × giganteus at most of the locations. Significant effects of the year of growth, location, species, genotype and interplay between these factors have been observed demonstrating strong genotype × environment interactions. The highest yields were recorded in Ukraine. Time needed for the crop establishment varied depending on climate: in colder climates such as Russia the crop has not achieved its peak yield by the fourth year, whereas in the hot climate of Turkey and under irrigation the yields were already high in the first growing season. We have identified several alternatives to M. × giganteus which have provided stable yields across wide climatic ranges, mostly interspecies hybrids, and also Miscanthus genotypes providing high biomass yields at specific geographic locations. Seed-propagated interspecific and intraspecific hybrids, with high stable yields and cheaper reliable scalable establishment remain a key strategic objective for breeders.